2014
DOI: 10.1063/1.4863485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of damping constant on inverse spin hall voltage of La0.7Sr0.3MnO3(x)/platinum bilayers

Abstract: Pure spin transport via spin pumping in the condition of ferromagnetic resonance can be transformed to charge current in the ferromagnetic/paramagnetic bilayer systems, based on inverse spin Hall effect (ISHE). Here, we explore LaSrMnO(x)/Pt(5.5 nm) [x = 10 to 65 nm] bilayers to investigate the influence of damping constant on spin pumping efficiency. The results show that the ISHE voltage depend on the damping constant of magnetic moment, suggesting that the precession energy tansferred to lattice/electron of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…Our results show that the damping constant of LSMO/Pt(5.5 nm) (α eff = 5.93 × 10 −3 ) is larger than LSMO(20 nm) (α eff = 1.57 × 10 −3 ). In comparison with the previous report on LSMO(20 nm)/Pt(5.5 nm), 14 the value of damping constant obtained from this work is 20 % lower. Considering the difference in the method of calulation in these two works, it is suggested that the value determined with the frequency dependence of resonance field (this work) should be more accurate than that with single frequence (Ref.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Our results show that the damping constant of LSMO/Pt(5.5 nm) (α eff = 5.93 × 10 −3 ) is larger than LSMO(20 nm) (α eff = 1.57 × 10 −3 ). In comparison with the previous report on LSMO(20 nm)/Pt(5.5 nm), 14 the value of damping constant obtained from this work is 20 % lower. Considering the difference in the method of calulation in these two works, it is suggested that the value determined with the frequency dependence of resonance field (this work) should be more accurate than that with single frequence (Ref.…”
Section: Resultsmentioning
confidence: 52%
“…To avoid the microwave heating, nitrogen gas keeps flowing into cavity during the measurement. The reason we have added this experimental step is because we observed a non-linear power dependence of ISHE voltage in previous work, 14 which was found to be related to the heating of LSMO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enlighted by our pioneer work on La 0.7 Sr 0.3 MnO 3 (LSMO)/Pt bilayers 25, 26 , it is realized that a systematic SP-FMR study should include all essential physical parameters for the investigated materials as well as a comprehensive analysis on FMR data, such that the origin of disagreement among reports could be self-prevailed. In this work we utilize the technique of cavity SP-FMR to investigate the intrinsic spin current properties on two series of LSMO/Pt bilayers with varying the thickness of LSMO and Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Manganite films for which the Curie temperature Tc is close to room temperature, especially attractive for practical applications. Although a number of studies have been carried out on the excitation of a spin current by ferromagnetic resonance in two LSMO/NM layer structures (NM is a normal metal, usually platinum) [9,10], there is no data on the temperature dependence of the width of the FMR line in the presence of spin current in ferromagnets.…”
Section: Introductionmentioning
confidence: 99%